The effect of novel antimicrobial agents on the normal functioning of human intestinal microbiota: a systematic review - Girma, Abayeneh (Frontiers in Gastroenterology, 2023)
Antimicrobial agents have significant effects on the ecological balance of the human microbiota through incomplete absorption (e.g., orally administered antimicrobial agents) or secretion (e.g., by the salivary glands, in the bile, or from the intestinal mucosa) of the agents. This study was aimed at examining the effects of novel antimicrobial agents on the normal functioning of the intestinal microbiota. The articles written in English were recovered from PubMed, ScienceDirect, Web of Science, Google Scholar, and DOAJ, as well as from manual searches using a reference list. "Microbiota", "Intestinal Microbiota", "Eubiotic Microbiota", "Ecological Impact", "Antimicrobial Agents,", "Antibiotics", "Dysbiosis", "Gut Microbiota," and "Probiotics" were the search terms used to retrieve the articles. The PRISMA-2009 checklist was applied for article search strategy, article selection, data extraction, and result reporting for the review process. A total of 8 original research articles were included from a total of 379 articles obtained in different search strategies. The eight new antimicrobial agents demonstrated significant impacts on the ecological balance of the human intestinal microbiota. Therefore, eubiosis is significantly crucial to prevent the establishment of exogenous antimicrobial-resistant strains as well as their gene transfer.